Development of Clostridium difficile R20291ΔPaLoc model strains and in vitro methodologies reveals CdtR is required for the production of CDT to cytotoxic levels - Bilverstone, T.W.; Kinsmore, N.L.; Minton, Nigel P.; Kuehne, Sarah A. (Elsevier, 2017)
Assessing the regulation of Clostridium difficile transferase (CDT), is complicated by the presence of a Pathogenicity locus (PaLoc) which encodes Toxins A and B. Here we developed R20291ΔPaLoc model strains and cell-based assays to quantify CDT-mediated virulence. Their application demonstrated that the transcriptional regulator, CdtR, was required for CDT-mediated cytotoxicity.